Energy Distribution in Tin Halide Perovskite. Issue 8 (10th December 2021) - Di Girolamo, Diego; Blundo, Elena; Folpini, Giulia; Ponti, Corinna; Li, Guixiang; Aldamasy, Mahmoud H.; Iqbal, Zafar; Pascual, Jorge; Nasti, Giuseppe; Li, Meng; Avolio, Roberto; Russina, Olga; et al.
Abstract : The power conversion efficiency of the formamidinium tin iodide (FASI) solar cells constantly increases, with the current record power conversion efficiency approaching 15%. The literature reports a broad anomaly distribution of the photoluminescence (PL) peak position. The PL anomaly is particularly relevant to photovoltaic applications since it directly links the material's bandgap and subgap defects energy, which are crucial to extracting its full photovoltaic potential. Herein, the PL of FASI polycrystalline thin film and powder is studied. It is found that a distribution of PL peak positions in line with the distribution available in the literature systematically. The distribution in PL is linked to the octahedral tilting and Sn off‐centering within the perovskite lattice, influenced by the procedure used to prepare the material. Our finding paves the way toward controlling the energy distribution of tin perovskite and thus preparing highly efficient tin halide perovskite solar cells. Abstract : The photoluminescence peak energy of polycrystalline formamidinium tin iodide perovskites is strongly dependent on the synthetic protocol, ageing, and oxidative stress, showing a broad distribution over more than 50 nm and slow dynamic behavior. Herein, the different sources of variation are identified and analyzed by comparing solid state synthesized powder to thin films.